THE IMPLEMENTATION OF RECONSTRUCTIVE AND AESTHETIC PLASTIC SURGERY AT RSUP H. ADAM MALIK MEDAN: COMPLIANCE WITH HEALTH REGULATIONS IN INDONESIA BASED ON LAW NO. 36 OF 2009 - Arya Tjipta Prananda; Fitri Rafianti; Bambang Fitrianto (PT. Sinergi Legal Publisher, 2024)
Plastic surgery, including reconstructive and aesthetic procedures, is increasingly significant in healthcare systems worldwide. In Indonesia, plastic surgery practices are governed by several health regulations, including the Health Law No. 23 of 1992 and the Medical Practice Law No. 19 of 2004. However, challenges in regulatory compliance and enforcement continue to affect patient outcomes. This study investigates how these procedures are implemented at RSUP H. Adam Malik Medan, particularly in light of existing health regulations. Using a qualitative approach, including interviews with healthcare professionals and patients, this research aims to identify gaps in legal compliance, patient safety, and ethical considerations in plastic surgery practices. The findings suggest a need for stronger regulatory oversight, better practitioner training, and improved patient education on informed consent and surgical risks.